205k views
2 votes
Simplify the expression.
13[6^2/(5^2 - 4^2)+9]​

User EPharaoh
by
5.1k points

2 Answers

4 votes

Answer:

169 aidan talk to meee

Explanation:

1.1 4 = 22

(4)2 = (22)2 = 24

(62)

13 • (————————— + 9)

(52 - 24)

3.1 6 = 2•3

(6)2 = (2•3)2 = 22 • 3 (22•32)

13 • (——————— + 9)

9 (22•32)

Simplify ———————

9

4.1 Canceling out 32 as it appears on both sides of the fraction line

13 • (4 + 9) gives you 169

User Doron Segal
by
5.2k points
5 votes

Answer:

The simplified term for the given expression is 169.

Explanation:

Solving within the parenthesis, given the expression:

13{6^2/(5^2-4^2)+9}

13{36/(25-16)+9}

13{36/9+9}

13(9+4)

13(13)

Therefore, the simplified term in terms of the expression, 13(6^2/5^2-4^2)+9), is 169.

User Kubilay
by
4.8k points